Natural language processing from scratch - Gonçalves, Bruno (Pearson, 2019)
"Natural Language Processing LiveLessons covers the fundamentals of natural language processing (NLP). It introduces you to the basic concepts, ideas, and algorithms necessary to develop your own NLP applications in a step-by-step and intuitive fashion. The lessons follow a gradual progression, from the more specific to the more abstract, taking you from the very basics to some of the most recent and sophisticated algorithms."--Resource description page
Title from title screen (viewed January 11, 2019)
Keywords: Natural language processing (Computer science); Natural Language Processing; Traitement automatique des langues naturelles